Spatial Ability in Mathematics Learning: A Systematic Review from the Perspective of Technology and Learning Models - Zulfa Dayyinati Fa'izulloh; Bambang Eko Susilo; Arief Agoestanto; Scolastika Mariani (Universitas Teknokrat Indonesia, 2026)
This study aims to examine the role of technology and learning models in improving students’ spatial abilities in mathematics learning. Using the Systematic Literature Review (SLR) method guided by the PRISMA framework, this study analyzed seven relevant articles published between 2020 and 2025 from reputable databases such as Google Scholar, Semantic Scholar, and SINTA. The findings indicate that various learning technologies, including GeoGebra, Augmented Reality (AR), Virtual Reality–based mobile learning, Math City Maps, and Adobe Flash, have a positive impact on supporting visualization, interaction, and students’ understanding of geometric and spatial concepts. In addition, constructivist-oriented learning models such as Problem Based Learning (PBL), Guided Discovery Learning, Contextual Teaching and Learning (CTL), the Van Hiele model, and Thinking Aloud Pair Problem Solving (TAPPS) provide more meaningful learning experiences by encouraging active exploration, discussion, and independent construction of spatial concepts. The results further demonstrate that the integration of interactive and immersive technologies with appropriate learning models produces a synergistic effect in enhancing students’ mathematical spatial abilities. These findings offer an important foundation for educators in designing mathematics instruction that is more innovative, contextual, and aligned with the characteristics of the digital generation. Future research is recommended to further investigate the effectiveness of specific combinations of technologies and learning models in authentic classroom settings